Comparative diagnostic accuracy of EUS needles in solid pancreatic masses: a network meta-analysis - Han, Samuel; Bhullar, Furqan; Alaber, Omar; Kamal, Ayesha; Hopson, Puanani; Kanthasamy, Kavin; Coughlin, Sarah; Archibugi, Livia; Thiruvengadam, Nikhil; Moreau, Christopher; Jin, David; Paragomi, Pedram; Valverde-López, Francisco; Nagpal, Sajan; Yazici, Cemal; Papachristou, Georgios; Lee, Peter J; Akshintala, Venkata; on behalf of the Collaborative Alliance for Pancreatic Education and Research (CAPER) (Endoscopy International Open, 2021)
Background and study aims Endoscopic ultrasound (EUS)-guided tissue sampling is the standard of care for diagnosing solid pancreatic lesions. While many two-way comparisons between needle types have been made in randomized controlled trials (RCTs), it is unclear which size and type of needle offers the best probability of diagnosis. We therefore performed a network meta-analysis (NMA) to compare different sized and shaped needles to rank the diagnostic performance of each needle.Methods We searched MEDLINE, EMBASE and Cochrane Library databases through August, 2020 for RCTs that compared the diagnostic accuracy of EUS fine-needle aspiration (FNA) and biopsy (FNB) needles in solid pancreatic masses. Using a random-effects NMA under the frequentist framework, RCTs were analyzed to identify the best needle type and sampling technique. Performance scores (P-scores) were used to rank the different needles based on pooled diagnostic accuracy. The NMA model was used to calculate pairwise relative risk (RR) with 95 % confidence intervals.Results Review of 2577 studies yielded 29 RCTs for quantitative synthesis, comparing 13 different needle types. All 22G FNB needles had an RR > 1 compared to the reference 22G FNA (Cook) needle. The highest P-scores were seen with the 22G Medtronic FNB needle (0.9279), followed by the 22G Olympus FNB needle (0.8962) and the 22G Boston Scientific FNB needle (0.8739). Diagnostic accuracy was not significantly different between needles with or without suction.Conclusions In comparison to FNA needles, FNB needles offer the highest diagnostic performance in sampling pancreatic masses, particularly with 22G FNB needles.